Model-independent D-0-(D)over-bar(0) mixing and CP violation studies with D-0 -> K-S(0)pi(+)pi(-) and D-0 -> (KSK+K-)-K-0 - Thomas, C; Wilkinson, G (2012)
Simulation studies are performed to assess the sensitivity of a model-independent analysis of the avour-tagged decays D 0 → K S0π +π - and D 0 → K S0K +K - to mixing and CP violation. The analysis takes as input measurements of the D decay strong-phase parameters that are accessible in quantum-correlated D-D̄ pairs produced at the Ψ (3770) resonance. It is shown that the model-independent approach is well suited to the very large data sets expected at an upgraded LHCb experiment, or future high luminosity e +e - facility, and that with 100M K S0π +π - decays a statistical precision of around 0:01 and 0:7° is achievable on the CP violation parameters r CP and α CP, respectively. Even with this very large sample the systematic uncertainties associated with the strong-phase parameters will not be limiting, assuming that full use is made of the available Ψ (3770) data sets of CLEO-c and BES-III. Furthermore, it is demonstrated that large avour-tagged samples can themselves be exploited to provide information on the strong-phase parameters, a feature that will be beneficial in the measurement of the CKM angle Γ/φ 3 with B - → DK - decays. © 2012 SISSA.